"Bridging Divides for Water": The 5th World Water forum (WWf) and the Alternative Water forum. (1st January 2009) - Ferragina, Eugenia
Abstract : The article reports on the activities and debates of the 5th World Water Forum held at Istanbul in March 2009. The Forum saw the participation of various international and financial organizations, and marked a further stage in the debate on the actions the international community needs to take for the sustainable management of water resources. The Forum's title, "Bridging Divides for Water", is a testimony of the centrality of the issue of unequal access to water resources at global level. The other themes regarded other major issues such as social inequalities and water as a denied right, the effects of climate change, water security, and water management and policies.